Grafia druków polskich z 1521 i 1522. Problemy wariantywności i normalizacji - Lisowski, Tomasz (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza, 2001)
The first six Polish prints of 1521 and 1522 (including two independent editions of Żywot Pana Jezu Krysta [The Life of Our Lord Jesus Christ] by Baltazar Opec) are discussed. Methods of graphemics were used, a grapheme was defined as a disposition to graphic substitution of a phoneme. The two competitive spelling systems are characterized - the functional one, capable of adequate rendition of phonetic reality of the then Polish language as used in Vietor's printing house and the conservative one, which refers to Bohemian spelling patterns used by Jan Sandecki. The degree of standardisation of Polish spelling at the beginning of the 16th century was determined.
Spelling of Polish prints of 1521 and 1522. Problems of variants and standardisation